TIP-OF-THE-TONGUE ANALYSIS IN INDONESIAN LANGUAGE SPEAKER: A CASE STUDY - Rahman, Azkia; Kushartanti, .; Anjarningsih, Harwinta (PEOPLE: International Journal of Social Sciences, 2017)
The phenomenon of ToT is an interesting issue to be studied more and more, especially in the field of Linguistics, since prior research on ToT is only studied in the realm of Psychology. Later in 1966, Brown and MacNeill became pioneers in ToT research. In Indonesia itself, research related to ToT is rarely done. That is what prompted the birth of this simple study, whose hope could later be developed for more complex and complete studies in similar fields. This study aims to explain the possibility of ToT and at what level of Indonesian speakers can recall the target word in ToT condition. Participants of this study were 10 people with age range 25-59 years with the category of adults according to WHO (World Health Organization) with the number of 5 men and 5 women. The theory used as the basis of the study is based on Brown and MacNeill (1966) ToT analysis. The results showed that when participants were indicated to have ToT conditions, they could recall similar letters, syllables and words that might be present in the given target word. Based on the above description we can conclude that participants with ToT conditions have access to their phonological knowledge, but not enough to activate the word as a whole and in ToT condition, the ability to recall the target word can be in word, syllable and letter level.